Going Out : Walking, Listening, Soundmaking - Biserna, Elena (Brussels : Umland, 2023)
Max Neuhaus, Willem de Ridder, William Levy, Collective Actions Group, David Helbich, Janet Cardiff, Jacek Smolicki, Carolyn Chen, Tao G. Vrhovec Sambolec, Hildegard Westerkamp, Albert Mayr, Tim Ingold, Akio Suzuki, katrinem, Beatrice Ferrara & Leandro Pisano, Catherine Clover, AM Kanngieser, Gascia Ouzounian & Sarah Lappin, Ultra-red, Vivian Caccuri, Stefan Szczelkun, LIGNA, Edyta Jarząb, Oupa Sibeko, Brian Hioe, Brandon LaBelle, Adrian Piper, Andra McCartney & Sandra Gabriele, Amanda Gutiérrez, Jennifer Lynn Stoever, Stephanie Springgay, Carmen Papalia, Christine Sun Kim, Charles Eppley, Budhaditya Chattopadhyay, Viv Corringham, BNA-BBOT, Ella Parry-Davies & Ann, Mendi + Keith Obadike, Gwenola Wagon & Stéphane Degoutin, Eleni Ikoniadou, Justin Bennett, Christina Kubisch & Christoph Cox, RYBN, Alisa Oleva, Naomi Waltham-Smith, Anna Raimondo, Libby Harward
Since the 1960s, the act of walking has provided a way for artists and musicians to escape the formality of the concert hall or institutional venue, engaging with shifting public spaces, natural environments, and the social and political sphere. Walking redefines notions of composer, performer, public, and music itself, while opening new modes of perception and action. Going Out addresses these developments by exploring the relationship between walking, listening, and soundmaking in the arts—from the first soundwalks and itinerant performances in the 1960s to today's manifold ambulatory projects. The book consists of an extensive essay by Elena Biserna followed by an anthology of historical and contemporary contributions in the form of documentation, essays, interviews, manifestos, scores, narratives, and reflections. Through the variety of these contributions, the book makes an argument that at the intersection of walking, listening, and soundmaking there is both a long legacy of interdisciplinary experimentations and a broad field that resounds with urgent issues in critical spatial thinking and practice.
boek